Determination of traits affecting the yield of Vicia Faba L. in two locations in the southern region under the influence of planting dates - Alsubahi, Waleed A. j. (Edelweiss Applied Science and Technology, 2024)
A field research study was conducted in two different locations in the southern region (Misan and Basrah) during the winter of 2021-2022 to identify the traits that had the greatest effect on the yield of native varieties of broad beans through path coefficient analysis. The seedlings of the stock were planted on three different dates (10/15, 11/01, 11/15). Using a random block design with 3 replications in each study location, the composition of yield and the total plant yield were evaluated in addition to the height and number of branches per plant. The results demonstrated that: Maysan's site had a superior performance in all traits studied, this was reflected in the highest yield per plant. (385.29) g/plant, while Basrah site provided a yield per plant of (282.1) g. In terms of planting date, the first date had the highest yield of 389.6 g, while the second and third dates provided yields of (384.99) and (219.26) g, respectively. The interaction between Maysan site and different planting dates produced higher yield than the interaction between Basrah site and date, and the interaction between Maysan site and the first date was the highest with a yield of (394.4) g/plant, while the yield of Basrah site with the third interaction date was the lowest with (198.4) g. The results of path coefficient analysis showed that the number of seeds per pod and the average number of pods were the two factors with the greatest impact on the faba bean crop, while the number of seeds and the number of pods had the least impact on the yield trait as they had higher yield traits. The significant positive correlation values were (0.830 and 0.674), while the correlation of the number of seeds per pod was (0.395). The direct effects of the number of seeds per pod and the number of pods per plant on these two traits were (0.812 and 0.710) and the indirect effects were (0.299 and 0.105). Therefore, these two traits can be used as a guide for the selection of programs. Breeding for improving faba bean yield.